Social Media, Gender and Politics: Public Perception of Female Politicians through the Facebook - Ogunmusire, Adebisi (Àgídìgbo: ABUAD Journal of the Humanities, 2021)
Social Media is a dynamic form of communication platform that gives rapid feedback to messages posted/sent to targeted receivers. However, as much as there seems to be a fairly remarkable acceptance of females in politics, there is still an assumption that responses gotten on their social media platforms particularly are biased and unbalanced compared with that of their male counterpart. This work (a short field communication) evaluates the perception of messages received by or posted on the social media platforms of female politicians by the Nigerian citizens, based on responses and reactions to the social media updates and posts of these female politicians, using Facebook, as a case study. With the use of content analysis, the accounts of four selected female presidential candidates were purposively selected and analysed using Pew Institute data). The results revealed the suspected imbalance but noted an increase the citizens’ awareness of the effects of gender prejudice. It however avers that this could change with time because of the noticeable people’s sensitivity to effects of the imbalance. The study concludes that the dynamic nature of the social media goes a long way in influencing the sensitivity to the female gender.